Problem Based Learning to Improve Students Ability in Listening in SMKS KR Ulususua - Laoli, Adieli; Zalukhu, Jepriaman; Saleh Laia, Putrawan; Kelvin Eferistus Albers Halawa, Zun (Blantika: Multidisciplinary Journal, 2025)
This study was motivated by the challenges faced by SMKS KR Ulususua students in developing their English listening skills, which negatively impacted their academic achievement. The purpose of this study was to investigate the effectiveness of problem-based learning (PBL) in improving students' listening skills. The method used was classroom action research with two cycles, involving 32 students of grade XI-A. Data were collected through listening ability tests, observations, and questionnaires. The results showed that the average score of students' listening skills increased from 65.3 in the pre-test to 82.4 in the second cycle post-test. In addition, student engagement in learning also increased, with 85% of students actively participating in PBL activities. The conclusion of this study is that the implementation of PBL significantly improves students' listening skills and encourages students' engagement and motivation in learning. This study recommends the integration of PBL in the vocational education curriculum to improve English learning outcomes.